Acute effects of a pre-season speed training program on sand vs. hard court in professional basketball players - Raasch, K.; Heil, J.; Vuong, J. L.; Ferrauti, A. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Basketball is known as a fast paced team sport, characterized by constant changes of direction as well as speed with acceleration and deceleration. Recently, sand as a training surface has gained in importance and an increasing amount of research is focused on the beneficial long-term effects on speed related training on sand [1; 2]. Considering that long-term effects are based on the acute internal and external loads, little research investigated the short-term effects of sand training. Therefore, the aim of this study was to compare the acute effects of a pre-season speed training on sand versus hard court on physiological load and neuromuscular performance in professional basketball players.